Paraneoplastic Leukemoid Reaction in High-Grade Lung Adenocarcinoma Complicated by Triple Co-Mutations - Kim L. Tran; Seema R. Walvekar; Brian C. Boulmay; Sarah W. Lungaro; Jasmine L. Taylor (Annals of Internal Medicine: Clinical Cases)
Paraneoplastic leukemoid reaction occurs secondary to cytokine-secreting tumors or cancers with high tumor burden. We report a case of extreme leukocytosis in a 58-year-old man presenting with a clavicular mass. Biopsy revealed a high-grade, non–small cell carcinoma of unknown origin, and genetic studies identified a lung adenocarcinoma with triple mutations in STK11, KRAS, and TP53 along with programmed death-ligand 1 positivity. Leukocytosis persisted despite treatment, so the diagnosis of paraneoplastic leukemoid reaction was made. Treatment of underlying malignancy is imperative in management, but this case was complicated by tumor mutations that rendered the most optimal treatments less effective.